2019
DOI: 10.1002/pola.29450
|View full text |Cite
|
Sign up to set email alerts
|

Maleimidophenyl isocyanates as postpolymerization modification agents and their applications in the synthesis of block copolymers

Abstract: The maleimide structure is highly reactive, exemplified by thiol–ene click reactions with thiols and Diels–Alder reactions with furans. Although postpolymerization modifications and macromolecular conjugations involving maleimide units have been widely studied, mostly due to their selectivity and high reactivity, little has been reported on the one‐pot postpolymerization introduction of maleimides in polymer chains. Herein, we report p‐maleimidophenyl isocyanate and its derivatives as modification agents to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Surprisingly, when N-aryl MA was used, the t gel occurred much earlier than when N-alkyl MA was used, indicating a higher reactivity of N-aryl MA PEG compared to that of N-alkyl MA PEG. In our previous work, 42 we found the reactivity of phenyl maleimide terminated PEG toward thiol molecule was as same as that of alkyl maleimide terminated PEG in chloroform with triethylamine as a base catalyst. To our best knowledges, this is first case that a difference in the reactivity of phenyl and alkyl N-substituted maleimide in water has been observed.…”
Section: Fabrication Of Tetrapeg Gels From N-aryl Ma-based Precursorsmentioning
confidence: 72%
See 2 more Smart Citations
“…Surprisingly, when N-aryl MA was used, the t gel occurred much earlier than when N-alkyl MA was used, indicating a higher reactivity of N-aryl MA PEG compared to that of N-alkyl MA PEG. In our previous work, 42 we found the reactivity of phenyl maleimide terminated PEG toward thiol molecule was as same as that of alkyl maleimide terminated PEG in chloroform with triethylamine as a base catalyst. To our best knowledges, this is first case that a difference in the reactivity of phenyl and alkyl N-substituted maleimide in water has been observed.…”
Section: Fabrication Of Tetrapeg Gels From N-aryl Ma-based Precursorsmentioning
confidence: 72%
“…We have recently developed one-pot post-polymerization modification reactions using p-maleimidophenyl isocyanate (PMPI) as a modification reagent to introduce maleimide moieties into polymers with hydroxy groups and studied the polymerization reactions between the introduced N-aryl MA groups and thiol groups. 42 Their high reactivity was corroborated by the kinetics of the addition reactions between the alcohols and isocyanates (-OH and -NCO) and the coupling of the obtained maleimide-terminated polymers with thiolterminated polymers (-MA and -SH). This procedure is very effective for the transformation of typical hydroxy groups in polymer chains into reactive MA groups, as the reaction is quantitative without any side reactions.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Functional glycoluril derivatives are available as the crosslinkers for the construction of network polymer systems . On the other hand, various compounds containing a reactive maleimide moiety are used for the syntheses of thermally stable copolymers with vinyl monomers by radical chain polymerization, high‐temperature polymer networks by successive addition reactions, and degradable and stimuli‐responsive network polymers by reversible Diels–Alder reactions . We previously reported that N ‐allylmaleimide (AMI) copolymers produced by radical copolymerization were valid as the precursor polymers for thermoset systems with or without crosslinking agents .…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] On the other hand, various compounds containing a reactive maleimide moiety are used for the syntheses of thermally stable copolymers with vinyl monomers by radical chain polymerization, [9][10][11][12][13][14][15][16][17][18] high-temperature polymer networks by successive addition reactions, [19][20][21][22][23][24][25] and degradable and stimuli-responsive network polymers by reversible Diels-Alder reactions. [26][27][28][29][30] We previously reported that Nallylmaleimide (AMI) copolymers produced by radical copolymerization were valid as the precursor polymers for thermoset systems with or without crosslinking agents. [31][32][33][34][35] The maleimide copolymers exhibited a high glass-transition temperature (T g ) and excellent thermal stability, but the cured materials were brittle.…”
mentioning
confidence: 99%